Imaging Observation of Ionospheric Field Aligned Irregularities by the PANSY Radar at Antarctic Syowa Station - Kagawa, Daisuke; Hashimoto, Taishi; Saito, Akinori; Nishimura, Koji; Tsutsumi, Masaki; Sato, Toru; Sato, Kaoru (2020)
The 11th Symposium on Polar Science/Interdisciplinary sessions: [IW] Whole atmosphere, Thu. 3 Dec. conference object